The Influence Of Waste Monitoring Officers On The Implementation Of Waste Management In Naimata Village, Kupang City In 2023 - Agustina, Agustina; Rahmawaty, Ety; Suluh, Debora G.; Mado, Fransiskus Geroda (International Journal of Health Sciences, 2024)
Based on initial research in RT 11 RW 4 Naimata Village, there is so much waste produced every day, but the waste produced is not managed properly but all the waste produced is directly burned. This type of research is descriptive, the variables in this study are Domestic Waste Management in the Naimata Village community. The population in this study was 600 families, the research sample was 381 families, data collection was carried out by survey using the Epicoleck application. Descriptive data analysis. The results of the study showed that the stages of waste management in Naimata Village did not meet the requirements where the waste management components that were measured or assessed were the Containment stage in the good category 56%, the Collection Stage there were 70% in the bad category, the processing category there were 89% in the bad category, and the variable rate of waste generation produced 98% of the waste produced> 2.5% L / O / H. The suggestion given is to try to build a TPSS in Naimata sub-district, so that the community can process waste properly.